Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.physletb.2012.10.076
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plasmon mass on spin light of neutrino in dense matter

Abstract: We develop the theory of spin light of neutrino in matter ($SL\nu$) and include the effect of plasma influence on the emitted photon. We use the special technique based on exact solutions of particles wave equations in matter to perform all the relevant calculations, and track how the plasmon mass enters the process characteristics including the neutrino energy spectrum, $SL\nu$ rate and power. The new feature it induces is the existence of the process threshold for which we have found the exact expression and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…We have termed this effect the "spin light of electron in neutrino flux" (SLe ν ) and considered the SLe ν radiation rate, power and emitted photon energy. The mechanism of the proposed new phenomenon is similar to one of the spin light of neutrino in matter (SLν) [3,4,5,6]. The latter effect is possible in the case of nonzero neutrino magnetic moments [7] (for a recent status of neutrino electromagnetic properties see a review [8]).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…We have termed this effect the "spin light of electron in neutrino flux" (SLe ν ) and considered the SLe ν radiation rate, power and emitted photon energy. The mechanism of the proposed new phenomenon is similar to one of the spin light of neutrino in matter (SLν) [3,4,5,6]. The latter effect is possible in the case of nonzero neutrino magnetic moments [7] (for a recent status of neutrino electromagnetic properties see a review [8]).…”
mentioning
confidence: 81%
“…For the SLν in matter these effects have been discussed in details in [5,6,16]. In [1,2] we have shown that the effect of nonzero emitted photon mass (the plasmon mass m γ ) in the case of SLe ν is not important, mγ Gnδ ≪ 1.…”
Section: Effect Of Plasmamentioning
confidence: 97%
“…The electromagnetic wave propagation in the background environment is influenced by the plasma effects. For the SLν in matter these effects have been discussed in details in [6,19,20]. In [14] we have shown that the effect of nonzero emitted photon mass (the plasmon mass m γ ) in the case of SLe ν is not important, mγ Gnδ 1.…”
Section: Effect Of Plasmamentioning
confidence: 99%
“…The spin light of neutrino [1] originates from the neutrino-photon magnetic moment coupling and from splitting of the neutrino energy over the helicity s = ±1, induced by external environment (see [2,3,4] and references therein). The total rate and power of the radiation in homogeneous neutron matter (far from the threshold, see below),…”
Section: The 39th International Conference On High Energy Physics (Icmentioning
confidence: 99%